Impacts of Climate Change and Human Perturbations on Organic Carbon Burial in the Pearl River Estuary Over the Last Century - Li, Wenpeng; Li, Xinxin; Zhao, Xin; Sun, Chengpeng; Nie, Tianyi; Hu, Yumei; Wang, Chunzai (Frontiers in Marine Science, 2022)
Estuaries have experienced significant changes due to global climate change and human perturbations since the last century. However, the climate and anthropogenic influence on the burial of sedimentary organic carbon (OC) in estuaries is still not understood well yet. Here, a 3-meter sediment core was taken from the Pearl River Estuary (PRE) in China. Depth profiles of both bulk OC and lignin biomarker data indicated three stages with different features of buried OC during the 130-year sediment deposition. The 1893-1957 stage showed 20% more burial of marine derived OC, which was mostly adsorbed on finer minerals compared to the years after 1957. The 1957-1980 period witnessed 4.6 times higher burial rate of petrogenic OC, which made the radiocarbon age of total organic carbon 42% older than before due to soil erosion and carbonate rock weathering. The 7-year running average variation of terrestrial OC input based on endmember mixing model was correlated with the Pacific Decadal Oscillation index before 1957, but correlated with the Atlantic Multidecadal Oscillation between 1957 and 1980 in the region. The reduction of land derived OC content after 1980s was mostly affected by human perturbations such as deforestation and dam construction which corresponded to the beginning of Economic Reform and Open Up in China. The overall increase of lignin content from bottom to surface sediment indicated increased vascular plant derived OC due to deforestation activities during the urbanization process. The study suggested different time periods when climate or human disturbance dominantly affected the OC burial in the PRE, which have significant indications for local and global carbon cycling and environmental ecology.